2011
DOI: 10.1111/j.1479-8425.2011.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep evaluation by a newly developed PVDF sensor non-contact sheet: a comparison with standard polysomnography and wrist actigraphy

Abstract: Polysomnographic (PSG) recording of multiple physiological measures remains the gold standard for sleep assessment in both basic and clinical human sleep research. However, PSG requires many unnatural conditions that can influence sleep phenomena. Recently, non-contact sheet sensors (SS) have been developed for sleep evaluation. Sheet sensor technology provides advantages over existing minimally intrusive devices used to analyze sleep-related behavior, such as wrist actigraphy (WA), beginning with freedom from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…The correlation analysis between sleep variables measured via SS and subjective sleep quality revealed that objective sleep time and sleep efficiency were correlated with subjective sleep quality ("initiation and maintenance of sleep", "refreshing," and "sleep length") upon waking. The reliability and validity of SSs have already been confirmed through simultaneous measurement with PSG and actigraphy [12]. Our data also supported the efficacy of SSs as an accurate method of measuring subjective sleep quality upon waking.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The correlation analysis between sleep variables measured via SS and subjective sleep quality revealed that objective sleep time and sleep efficiency were correlated with subjective sleep quality ("initiation and maintenance of sleep", "refreshing," and "sleep length") upon waking. The reliability and validity of SSs have already been confirmed through simultaneous measurement with PSG and actigraphy [12]. Our data also supported the efficacy of SSs as an accurate method of measuring subjective sleep quality upon waking.…”
Section: Discussionsupporting
confidence: 80%
“…Although polysomnography (PSG) is the gold standard for objective sleep evaluation, the method involves attaching electrodes to the head, which can inhibit natural sleep and can be difficult to conduct at home. Non-contact sheet sensors (SSs) are a recently-developed type of sensor confirmed to have the reliability and validity of PSG and actigraphy [12]. Thus, SSs constitute a convenient method for collecting sleep data, and can facilitate diagnoses, evaluations of treatment, and clinical research on sleep disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The AG underestimated SOL by 19.7 min, compared to PSG, which is similar to previous studies on healthy adults, regardless of the device or algorithm used [12,21,28,29,[36][37][38][41][42][43][44][45][46][47][48]. Studies using the ActiGraph GT3X+ and Cole-Kripke algorithm have reported underestimations of SOL ranging from 6.4 to 15.1 min [19,28,36,46].…”
Section: Sleep Onset Latencysupporting
confidence: 86%
“…Emerging wearable bioelectronics are garnering substantial interest in recent decades due to their portability, wearability, and capability of providing continous monitoring, [23][24][25][26][27][28][29] which make them potential solutions in making up for the deficiency of PSG in sleep monitoring. [30][31][32][33][34] To date, wearable and flexible sensors with different working mechanisms, such as piezoelectric, [35] ferroelectric, [36] resistive, [37][38][39][40] capacitance [41,42] and triboelectric, [43][44][45][46][47][48][49] magnetoelastic [50][51][52][53][54] have been developed for wearable biomechanical sensing, which also shows remarkable ability to monitor respiratory signals during sleep. Table S1, Supporting Information shows representative technical indicators of these work on respiration monitoring.…”
Section: Introductionmentioning
confidence: 99%